Effect of inplane boundary constraints on the response of thick general (unsymmetric) cross-ply plates - Oktem, Ahmet Sinan; Chaudhuri, Reaz A. (ELSEVIER SCI LTD, 2008)
A hitherto unavailable HSDT (higher-order shear deformation theory)-based boundary-discontinuous Fourier solution to the class of problems of general cross-ply plates that cannot be solved using the classical Navier or Levy type approach is presented. A self-adjoint differential system of five highly coupled fourth-order linear partial differential equations, subjected to SS1 and SS4-type simply supported boundary conditions prescribed at all four edges, is solved analytically using the boundary-discontinuous double Fourier series technique. The numerical accuracy of the solution is ascertained by studying the convergence characteristics of deflections and moments of an antisymmetric cross-ply plate. The primary focus of the present study is to investigate the effect of inplane boundary constraints on the response of a thick asymmetrically laminated cross-ply plate, while keeping the remaining end constraints unaltered. Important numerical results presented include sensitivity of the predicted response quantities of interest to lamination, material property, thickness effects and inplane end constraint as well as their interactions. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: thick laminate; higher-order shear deformation theory (HSDT); cross-ply; analytical solution; boundary-discontinuous double Fourier series; inplane end constraints; HIGHER-ORDER THEORY; MODERATELY THICK; FREQUENCY-RESPONSE; FOURIER-ANALYSIS; FREE-VIBRATION; DEFORMATION; SHELL; Mechanics; Materials Science